2017
DOI: 10.1080/09638288.2017.1327987
|View full text |Cite
|
Sign up to set email alerts
|

Pain management for children with cerebral palsy in school settings in two cultures: action and reaction approaches

Abstract: Differences might be due to school- and healthcare systems. To provide effective support when children with CP are in pain in school settings, an action-and-reaction approach would be optimal and the use of alternative and augmentative communication strategies would help to communicate children's pain. As prevention of pain is desired, structured surveillance and treatment programs are recommended along with trustful collaboration with parents and access to "hands-on" pain management when needed. Implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 62 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…In recent studies, professionals (teachers and therapists) working with children with CP in school settings in South Africa and Sweden were asked about the intervention strategies they used to manage the children’s recurrent pain in school settings (Adolfsson et al 2018; Johnson et al 2015; Nilsson et al 2016). The professionals in the said studies reported on a variety of intervention strategies.…”
Section: Intervention Strategies In South African School Settingsmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent studies, professionals (teachers and therapists) working with children with CP in school settings in South Africa and Sweden were asked about the intervention strategies they used to manage the children’s recurrent pain in school settings (Adolfsson et al 2018; Johnson et al 2015; Nilsson et al 2016). The professionals in the said studies reported on a variety of intervention strategies.…”
Section: Intervention Strategies In South African School Settingsmentioning
confidence: 99%
“…The professionals in the said studies reported on a variety of intervention strategies. Subsequently, action-and-reaction approaches followed by healthcare professionals during pain management were identified (Adolfsson et al 2018). Action refers to strategies professionals use to prevent pain, while reaction refers to professionals’ strategies to intervene when a child is already experiencing pain.…”
Section: Intervention Strategies In South African School Settingsmentioning
confidence: 99%
See 3 more Smart Citations